Use of life support in acutely admitted ICU patients. An international cohort study. Issue 5 (10th March 2017) - Meyhoff, T. S.; Krag, M.; Hjortrup, P. B.; Perner, A.; Møller, M. H.; ,
Abstract : Background: Use of life support in intensive care unit (ICU) patients has been associated with increased risk of poor outcome. The prognostic importance of the duration of support is less studied. We assessed the use of life support and the association between its duration and 90‐day mortality in a contemporary cohort of acutely admitted adult ICU patients. Methods: We performed a post‐hoc analysis of the SUP‐ICU 7‐day inception cohort study ( n = 1034), which was conducted in 97 ICUs in 11 countries. We included patients with an ICU stay of 3 days or more. We assessed the use of life support during the first 3 days in ICU and the crude and adjusted association between its duration and 90‐day mortality using logistic regression analyses. Results: We included 690 patients; their 90‐day mortality was 23%. During the first 3 days in ICU mechanical ventilation was used in 65%, vasopressors/inotropes in 57% and renal replacement therapy in 13%. Renal replacement therapy for 3 days or more was associated with a higher 90‐day mortality as compared with 1 day of renal replacement therapy [odds ratio 6.5 (95% confidence interval 1.3 to 32.8)]. For mechanical ventilation and vasopressors/inotropes the odds ratios were 2.2 [0.9 to 5.3] and 1.2 [0.5 to 2.6], respectively. Conclusions: Among acutely admitted adult ICU patients, a higher number of days of renal replacement therapy in the initial ICU stay were associated with increased risk of death within 90 days. We did not observe such an association for mechanical ventilation or vasopressor/inotropic therapy.